1997
DOI: 10.1074/jbc.272.32.19666
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylyl Cyclase-activating Peptide Stimulates Extracellular Signal-regulated Kinase 1 or 2 (ERK1/2) Activity in a Ras-independent, Mitogen-activated Protein Kinase/ERK Kinase 1 or 2-dependent Manner in PC12 Cells

Abstract: Sustained activation of extracellular signal-regulated kinase 1/2 (ERK1/2) is critical for initiating differentiation of the PC12 cell to a sympathetic-like neurone. The neuropeptide, pituitary adenylyl cyclase-activating peptide (PACAP), has been demonstrated to cause cells to adopt a neuronal phenotype, although the mechanism of this activity is unclear. PACAP through its type I receptor stimulates a biphasic activation of ERK1/2; a >10-fold increase within 5 min, followed by a >5-fold increase that is susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
104
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 30 publications
(18 reference statements)
7
104
0
Order By: Relevance
“…This finding will hopefully help to solve some of the "apparent discrepancies" (52) found in the literature on the mechanism of stimulation of the ERK pathway by Rap1 in neuronal cells. These data also reconciled previous reports with respect to the role of the cAMP pathway in PACAP-versus forskolin-induced ERK activation in PC12 cells (5,6,36,58). Finally, our data shed new light on the control of Rap1 activity by GPCRs, an important event in the context of neuronal differentiation.…”
Section: Dominant-negative Mutants Of Ras and Raf Prevent The Potentisupporting
confidence: 74%
See 1 more Smart Citation
“…This finding will hopefully help to solve some of the "apparent discrepancies" (52) found in the literature on the mechanism of stimulation of the ERK pathway by Rap1 in neuronal cells. These data also reconciled previous reports with respect to the role of the cAMP pathway in PACAP-versus forskolin-induced ERK activation in PC12 cells (5,6,36,58). Finally, our data shed new light on the control of Rap1 activity by GPCRs, an important event in the context of neuronal differentiation.…”
Section: Dominant-negative Mutants Of Ras and Raf Prevent The Potentisupporting
confidence: 74%
“…Pac1 displays a complex pattern of alternative splicing that modulates its ligand binding and signaling properties (31)(32)(33)(34) resulting in the modulation of PACAP physiological effects (28,35). We and others (21,31) showed that Pac1 potently stimulated the AC and PLC activities as well as the ERK pathway that was implicated in its neurotrophic activity (23,36). In this context, we selected the PC12 cell line to assess the involvement of the small GTP-binding proteins Rap1 and Ras in the signaling pathways responsible for PACAP-induced ERK activation in this system.…”
mentioning
confidence: 99%
“…In PC12 cells, tmACs can be activated by pituitary adenylyl cyclase-activating peptide (PACAP) via its specific G protein-coupled receptor PAC1 (12). Similar to NGF, PACAP activates Rap1 and elicits neurite outgrowth (13)(14)(15), but all attempts to link NGF or its receptors to tmAC activation have been unsuccessful. We have identified an additional, ubiquitously expressed (17,18) source of cAMP in mammalian cells, "soluble" adenylyl cyclase (sAC) (16).…”
mentioning
confidence: 99%
“…In Drosophila muscle, PACAP induces synaptic currents through the co-activation of adenylyl cyclase and p21 ras (Zhong, 1995). In contrast, PC12 neurite outgrowth is independent of cAMP-dependent protein kinase (PKA) and p21 ras (Barrie et al 1997). This study investigated the signalling pathways coupling PACAP receptors to Ca2+ influx in PC12 cells.…”
mentioning
confidence: 99%
“…This study investigated the signalling pathways coupling PACAP receptors to Ca2+ influx in PC12 cells. Experiments employed PC12 cells and a dominant negative Ras cell line (PC12asn17-W7) (Barrie et al 1997). Cytosolic [Ca2+] was recorded from cell suspensions loaded with 6 J1M fura-2 AM.…”
mentioning
confidence: 99%